Gillies temporal acess surgical technique for closed zygomatic arch reduction - Natália Barbosa de Siqueira; Mateus Barros Cavalcante; Bruno Coelho Mendes; João Victor Soares Rodrigues; Caroline Brígida Sá Rocha; Joana de Angelis Alves Silva; Eduardo Hochuli-Vieira (Revista Sul-Brasileira de Odontologia, 2022)
Fracture of the zygomatic arch is one of the most common facial bone fractures. By means of minimally invasive surgeries it is intended to preserve anatomical structures to the maximum, without extensive incisions or dissections, providing the best functional results with less operative trauma, the Gillies approach being widely used in this regard. Objective: To report a clinical case of a patient with a zygomatic arch fracture, in which a reduction was used through the temporal access of Gillies, as well as, guide the surgeon in treatment planning. Case report: Patient AFL, 62 years old, male, was referred to the Maxillofacial Surgery and Traumatology Service of the Restauração Hospital (Recife / PE), with a history of falling from a height, evolving with fracture of the left zygomatic arch, treated by closed reduction through the temporal access of Gillies. Results: In this way, the Gillies approach proved to be a rather traumatic technique, effective in our case, restoring esthetics and function with minimally invasive surgery. Conclusion: It is effective in our case, restoring aesthetics and function with minimally invasive surgery.